Genetic prediction of ICU hospitalization and mortality in COVID‐19 patients using artificial neural networks. Issue 5 (22nd January 2022) - Asteris, Panagiotis G.; Gavriilaki, Eleni; Touloumenidou, Tasoula; Koravou, Evaggelia‐Evdoxia; Koutra, Maria; Papayanni, Penelope Georgia; Pouleres, Alexandros; Karali, Vassiliki; Lemonis, Minas E.; Mamou, Anna; Skentou, Athanasia D.; Papalexandri, Apostolia; et al.
Abstract: There is an unmet need of models for early prediction of morbidity and mortality of Coronavirus disease‐19 (COVID‐19). We aimed to a) identify complement‐related genetic variants associated with the clinical outcomes of ICU hospitalization and death, b) develop an artificial neural network (ANN) predicting these outcomes and c) validate whether complement‐related variants are associated with an impaired complement phenotype. We prospectively recruited consecutive adult patients of Caucasian origin, hospitalized due to COVID‐19. Through targeted next‐generation sequencing, we identified variants in complement factor H/ CFH, CFB, CFH ‐ related, CFD, CD55, C3, C5, CFI, CD46, thrombomodulin / THBD, and A Disintegrin and Metalloproteinase with Thrombospondin motifs (ADAMTS13) . Among 381 variants in 133 patients, we identified 5 critical variants associated with severe COVID‐19: rs2547438 ( C3 ), rs2250656 ( C3 ), rs1042580 ( THBD ), rs800292 ( CFH ) and rs414628 ( CFHR1 ). Using age, gender and presence or absence of each variant, we developed an ANN predicting morbidity and mortality in 89.47% of the examined population. Furthermore, THBD and C3a levels were significantly increased in severe COVID‐19 patients and those harbouring relevant variants. Thus, we reveal for the first time an ANN accurately predicting ICU hospitalization and death in COVID‐19 patients, based on genetic variants in complement genes, age and gender. Importantly, we confirm that genetic dysregulation is associated with impaired complement phenotype.